2017
DOI: 10.1080/07315724.2017.1320951
|View full text |Cite
|
Sign up to set email alerts
|

Low 25-Hydroxyvitamin D and Myofascial Pain: Association of Cancer, Colon Polyps, and Tendon Rupture

Abstract: Myofascial pain as assessed by tender trigger points and 25(OH)D deficiency showed a significant association with cancer, adenomatous colon polyps, and tendon rupture. Further studies to verify these results are needed, especially in areas where there is low magnesium in the drinking water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 58 publications
0
3
0
2
Order By: Relevance
“…Epidemiological studies conducted on colorectal cancer (CRC) provided strong support for inverse association between serum 25(OH)D level and colon cancer risk in both men and women 39 , 40 , 41 , 42 . A cross-sectional study indicated that low concentration of 25(OH)D in serum was significantly associated with adenomas or colon polyps 43 . A meta-analysis showed that higher circulating 25(OH)D levels predicted decrease cancer death of CRC patients 44 .…”
Section: Potentiating Vitamin D As An Anticancer Agentmentioning
confidence: 99%
“…Epidemiological studies conducted on colorectal cancer (CRC) provided strong support for inverse association between serum 25(OH)D level and colon cancer risk in both men and women 39 , 40 , 41 , 42 . A cross-sectional study indicated that low concentration of 25(OH)D in serum was significantly associated with adenomas or colon polyps 43 . A meta-analysis showed that higher circulating 25(OH)D levels predicted decrease cancer death of CRC patients 44 .…”
Section: Potentiating Vitamin D As An Anticancer Agentmentioning
confidence: 99%
“…Günümüzde birçok hastalığın etiyolojisinde D vitamini eksikliği (DVE) olduğu düşünülmektedir (1)(2)(3)(4)(5)(6). Vitamin D 3 öncelikle deride sentezlenir ve karaciğerde hidroksillenerek 25 (OH) vitamin D'yi oluşturur (7)(8)(9)(10).…”
Section: Introductionunclassified
“…Erişkin yaşlarda patognomonik bulgusu bulunmamaktadır (11,13,16). Sıklıkla halsizlik, yorgunluk, duygu-durum bozukluğu, kaslarda huzursuzluk hissi, ağrı ve kramp tarzı belirtiler gösterebilir (1,3,10). D vitamini yetersizliğine bağlı oluşan osteomalazi kliniğinde genellikle lomber bölgeden başlayarak pelvis, uyluk, sırt ve kostaları içeren yaygın ağrılar görülür (3,14).…”
Section: Introductionunclassified
“…The role of magnesium as a cofactor for numerous enzymes, its impact on CNS function, and its ability to antagonize NMDA Glu receptors underscore its relevance in depression management [118,156,157]. Magnesium deficiency can lead to NMDA receptor hyperactivity, contributing to the development of depressive and anxiety-like symptoms and increased inflammatory markers [158].…”
Section: Magnesiummentioning
confidence: 99%